THE CHALLENGE FOR THE DEVELOPMENT OF PROFESSIONAL GUIDANCE – NEW PROFESSIONS IN THE LABOUR MARKET - Nazelskis, Eugenijus (Acta Paedagogica Vilnensia, 2011)
The article deals with the increase of general importance in the functioning of labour market in the circumstances of globalization and technological changes. It is proved that teoretical boundaries of professional guidance are expanding because labour organizations dispite their founders or capital belongness, become undevideble part of the whole system of professional guidance. It is stressed that in changing cirtumstances the importance of introducing new professions into the labour market is growing. Variations of professions, the appearance of new professions and their introduction into labour market, disproportion between needs and offers in labour market – all that become an extra challenge for the development of the system of professional guidance. Having in mind expectations of new professions and the importance of their introduction into the labour market, the author on the conceptual level gives suggestions to use online analytical processing for introducing new professions into the labour market. The strategical aim for labour management is not only psychological-pedagogical assistance for an individual in choosing a profession but also balancing needs and offers in the labour market by means of professional guidance.